2014
DOI: 10.5194/hessd-11-3857-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale regionalization of water table depth in peatlands optimized for greenhouse gas emission upscaling

Abstract: Abstract. Fluxes of the three main greenhouse gases (GHG) CO2, CH4 and N2O from peat and other organic soils are strongly controlled by water table depth. Information about the spatial distribution of water level is thus a crucial input parameter when upscaling GHG emissions to large scales. Here, we investigate the potential of statistical modeling for the regionalization of water levels in organic soils when data covers only a small fraction of the peatlands of the final map. Our study area is Germany. Phrea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The intensive management could refer to peat mining (though marginal peat cutting was accepted), deep drainage, and other attempts to change the land use for more than 10–20 years. The monitoring well (for groundwater table depth sites) being perforated only over the first 1 or 2 m or with the perforated section of the tube ending within the peat layer. We emphasize that this criterion is particularly important because national authorities typically maintain only groundwater monitoring networks with monitoring wells that penetrate deeply and cut through the peat layer, producing observations that are not representative of the peat layer (Bechtold et al, ).…”
Section: Model Experimental Setupmentioning
confidence: 99%
“…The intensive management could refer to peat mining (though marginal peat cutting was accepted), deep drainage, and other attempts to change the land use for more than 10–20 years. The monitoring well (for groundwater table depth sites) being perforated only over the first 1 or 2 m or with the perforated section of the tube ending within the peat layer. We emphasize that this criterion is particularly important because national authorities typically maintain only groundwater monitoring networks with monitoring wells that penetrate deeply and cut through the peat layer, producing observations that are not representative of the peat layer (Bechtold et al, ).…”
Section: Model Experimental Setupmentioning
confidence: 99%
“…(2019) already suggested, a module for drained northern peatlands (PEATCLSM North,Drain ) is needed to accurately model the role of peatlands in the global water and carbon cycles. In this research, we showed that following the same approach as for natural peatlands, a PEATCLSM North,Drain module could be achieved by developing a separate parameter set for northern drained peatlands, though drainage and water management practices are very diverse (Bechtold et al., 2014).…”
Section: Discussionmentioning
confidence: 99%